Sea Urchin as a Universal Model for Studies of Gene Networks - Adonin, Leonid; Drozdov, Anatoliy; Barlev, Nickolai A. (Frontiers in Genetics, 2021)
Purple sea urchin Strongylocentrotus purpuratus has been used for over 150 years as a model organism in developmental biology. It has been widely used for studying mechanisms of cell adhesion, cell cycle control mechanisms, calcium signaling, fertilization, cell differentiation, and cell survival and death. Massive parallel sequencing of the sea urchin genome allowed the deciphering of the main components of gene regulatory networks during the activation of embryonic signaling pathways. This knowledge helped to extrapolate aberrations in somatic cells that may lead to diseases, including cancer in humans. Furthermore, since many if not all developmental signaling pathways were shown to be controlled by non-coding RNAs, the sea urchin organism represents an attractive experimental model. In this review, we discuss the main discoveries in the genetics, genomics, and transcriptomics of sea urchin during embryogenesis with the main focus on the role of non-coding RNAs. This information may be useful for comparative studies between different organisms and help identify new regulatory networks controlled by non-coding RNAs.